2012
DOI: 10.2147/ijn.s29712
|View full text |Cite
|
Sign up to set email alerts
|

Lipidic nanocapsule drug delivery: neuronal protection for cochlear implant optimization

Abstract: Objective: Sensorineural hearing loss leads to the progressive degeneration of spiral ganglion cells (SGC). Next to postoperative fibrous tissue growth, which should be suppressed to assure a close nerve-electrode interaction, the density of healthy SGC is one factor that influences the efficiency of cochlear implants (CI), the choice of treatment for affected patients. Rolipram, a phosphodiesterase-4 inhibitor, has proven neuroprotective and anti-inflammatory effects and might also reduce SGC degeneration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 48 publications
(42 reference statements)
1
22
0
Order By: Relevance
“…They showed that lipid NP-encapsulated rolipram led to higher SGC survival rates and neurite outgrowth than rolipram delivery alone [25]. While rolipram may be studied in the future as a potential therapeutic agent, the findings of this study could not be replicated in vivo , which the authors believe may be due to non-sustained and nonspecific rolipram delivery.…”
Section: Applications Of Nanotechnology To Sensorineural Hearing Lmentioning
confidence: 86%
See 1 more Smart Citation
“…They showed that lipid NP-encapsulated rolipram led to higher SGC survival rates and neurite outgrowth than rolipram delivery alone [25]. While rolipram may be studied in the future as a potential therapeutic agent, the findings of this study could not be replicated in vivo , which the authors believe may be due to non-sustained and nonspecific rolipram delivery.…”
Section: Applications Of Nanotechnology To Sensorineural Hearing Lmentioning
confidence: 86%
“…Thus, current research is aimed at finding biomaterials that will increase neuronal survival and potentiate neurite outgrowth as a means of treating specific forms of neural hearing loss. [2528]. …”
Section: Inner Ear Anatomy and Physiologymentioning
confidence: 99%
“…A previous study of our group demonstrated a protective effect on SGN in vitro only if Rolipram was delivered encapsulated in lipid nanocapsules [49]. However, this neuroprotective effect was not observed after treatment with pure Rolipram [49].…”
Section: Introductionmentioning
confidence: 70%
“…A previous study of our group demonstrated a protective effect on SGN in vitro only if Rolipram was delivered encapsulated in lipid nanocapsules [49]. However, this neuroprotective effect was not observed after treatment with pure Rolipram [49]. One explanation could be that the used Rolipram concentration induced an increase of cAMP too high to promote the protective effect demonstrated by cAMP analogues [28][30].…”
Section: Introductionmentioning
confidence: 84%
“…However, even with the introduction of minimally traumatic “soft” surgical techniques (reviewed in [ 5 ] and [ 6 ]) and electrodes that have been modified to reduce intracochlear trauma during their insertion [ 7 ], residual hearing is lost or incompletely preserved in one-third of cases [ 8 ]. Some researchers have begun to explore the possibility that better hearing preservation may be achieved by the application of protective pharmacological agents to the inner ear at the time of surgery ([ 9 , 10 ] and [ 11 ], reviewed in [ 6 ]).…”
Section: Introductionmentioning
confidence: 99%